2014
DOI: 10.24908/ss.v12i2.4605
|View full text |Cite
|
Sign up to set email alerts
|

From self-tracking to smart urban infrastructures: towards an interdisciplinary research agenda on Big Data

Abstract: Recent debates on surveillance have emphasised the now myriad possibilities of automated, software-based data gathering, management and analysis. One of the many terms used to describe this phenomenon is ‘Big Data’. The field of Big Data covers a large and complex range of practices and technologies from smart borders to CCTV video analysis, and from consumer profiling to self-tracking applications. The paper’s aim is to explore the surveillance dynamics inherent in contemporary Big Data trends. To this end, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 41 publications
0
37
0
5
Order By: Relevance
“…Big data enables corporations, through experimentation with analytics, and the offering of applications which gather data on individuals, not only to collect and store their details but also encourage them to live in new ways. As Savage (2013) has identified and Klauser and Albrechtslund (2014) have argued, data analytics are much more lively and inuse, closely aligned with embodied life as it unfolds. By using the notions of proximity which arise in Merleau-Ponty (1968) and Levinas (1969), and by synthesizing extant empirical work on the experience of surveillance, we have suggested that, in an age of big data, where devices stream huge amounts of information about individuals to organizations, the surveilled subject can be understood in a new way.…”
Section: Conclusion: Towards a Politics Of Proximitymentioning
confidence: 99%
See 1 more Smart Citation
“…Big data enables corporations, through experimentation with analytics, and the offering of applications which gather data on individuals, not only to collect and store their details but also encourage them to live in new ways. As Savage (2013) has identified and Klauser and Albrechtslund (2014) have argued, data analytics are much more lively and inuse, closely aligned with embodied life as it unfolds. By using the notions of proximity which arise in Merleau-Ponty (1968) and Levinas (1969), and by synthesizing extant empirical work on the experience of surveillance, we have suggested that, in an age of big data, where devices stream huge amounts of information about individuals to organizations, the surveilled subject can be understood in a new way.…”
Section: Conclusion: Towards a Politics Of Proximitymentioning
confidence: 99%
“…As part of smart city infrastructures (Klauser and Albrechtslund, 2014), for example, smart meters allow householders to analyse and hence manage their electricity consumption. However, this information is also available to electricity suppliers and other partners involved in smart city projects.…”
Section: 'Big Data': the Terms Of Referencementioning
confidence: 99%
“…It needs to be noted, that surveillance and behavior change are heavily debated topics (cf. [16], [17]), which we will only touch upon in the context of this paper.…”
Section: Mobility Monitoring For Sustainabilitymentioning
confidence: 99%
“…Whilst urban studies has a long tradition of critically examining the interface between space and digital technologies (Graham, 2002;Graham and Marvin 1999;Boyer, 1992;Crang, 2010;Crang and Graham, 2007;Thrift and French, 2002), and information studies has targeted the city as one of its key domains of study (Forlano, 2009;Foth, 2009;Galloway, 2004;Middleton and Bryne, 2011), narratives and practices around notions of 'smartness' have been largely absent. In this context a limited number of practitioners and scholars are starting to question the problem-solving powers of 'smart', by asking questions around democracy and citizenship (Townsend, 2013;Greenfield, 2013;Halpern et al, 2013), drawing attention to the specific mechanisms through which code operates (Kitchin and Dodge, 2011), pointing to the risks of big data and a city with 'sensory capabilities' (Thrift, 2014a;2014b;Klauser and Albrechtslund, 2014) and examining how smart rationalities and techniques alter contemporary functionings of power, space and regulation (Klauser, 2013). More recently, scholars working on the interface between politics, life and the environment -drawing on post-structuralist thinking and often outside the world of urban geography-have been examining the ways in which the material manifestations of such smart logics (through, for example, the ubiquity of environmental sensors and dashboards) are transforming modes of governing both the city and society as a whole (Braun, 2014;Gabrys, 2014).…”
Section: Critical Gaps In Understanding Smart Urbanismmentioning
confidence: 99%